WOMENS OPPRESSION AND LIBERATION IN SEFI ATTAS EVERYTHING GOOD WILL COME - AYU PURI RAHAYU (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
Sefi Atta as one of Nigerian famous writers has made an honorable literary work entitled Everything Good Will Come. Atta was trying to portray the life of men and women under a patriarchal society. Women that are regarded as second class citizens are being oppressed by the superior class, in this case, men are taking the part as their oppressor. This study will focus on revealing how oppression is happened to female characters, done by male characters. Irish M. Young’s founding will be used to identify different types of oppression that are experienced by women. Young divides oppression into five structures; exploitation, marginalization, powerlessness, cultural imperialism, and violence. The analysis exposes that the events in the novel indicate the existence of oppression that comes across each female character in the novel, per character might face a different combination of oppression’s structures. Other than oppression, this study will also unveil women’s attempts to liberate themselves from oppression. Since Nigeria still strongly embraces patriarchal culture, a patriarchal theory will be applied, a theory coined by Sylvia Walby will come as an assist to reveal how women are living in a patriarchal society which can be the source of their repressions. Walby also points out her arguments about several egressions that women can do to free themselves from patriarchy. Some of Walby’s commentaries will be applied to this study as guidance to name the female characters’ struggles such as do the decision-making for their own lives, education, career improvisation, and divorcement to fight against male supremacy. Keywords: Oppression, Patriarchy, Liberation, Radical Feminism.